The Effect of Resistance Training on Muscle Strength and VO2 Peak in Middle-aged and Older Patients with Heart Failure: A Meta-analysis - Caroline Korengkeng, Loura; Anderson, Elisa; Yoan Sanger, Ailine; Ruku, Denny (Pacific Rim International Journal of Nursing Research, 2024)
Several interventions using resistance training have been attempted for people with heart failure. Still, the overall effectiveness of resistance training in improving muscle strength and peak oxygen uptake based on age remains inconclusive. This study aimed to investigate the efficacy of resistance training on muscle strength and VO2 peak in patients with heart failure based on age. A search was conducted using English articles from 2000 to 2023 to find information on resistance training from Embase, CINAHL, MEDLINE, Cochrane, PEDro, and Google Scholar. Standardized mean difference and 95% confidence intervals were calculated, and publication biases were presented by funnel plots and Egger’s test. The Critical Appraisal Skills Programme was used to examine the quality of the studies. Results showed that 23 randomized control trial articles fulfilled the inclusion criteria, comprising 830 respondents, with 422 in the intervention and 408 in the control group. In the middle-aged subgroup, resistance training had a significant effect on increasing muscle strength in the upper limb and lower limb. Similarly, a significant effect was observed in the older subgroup for the upper limb and lower limb. Resistance training significantly increased VO2 peak in middle-aged and older patients with heart failure. Resistance training was identified as one of the effective ways to improve muscle strength and VO2 peak, and it should be recommended as a part of the rehabilitation for people with heart failure. Additionally, the components of interventions should be considered based on the patient’s age to maximize the exercise programs using resistance training.